MASLAHAH-BASED AGENCY: AN EPISTEMOLOGICAL CRITIQUE OF INDIVIDUALISTIC RATIONALITY IN CONVENTIONAL AGENCY THEORY - Amirudin; Sumarlin; Abdullah, Wahyuddin (Yayasan Nuraini Ibrahim Mandiri, 2025)
Conventional agency theory, rooted in the assumptions of individualistic rationality and contractual relations between principals and agents, exhibits fundamental limitations when applied to Islamic financial systems that emphasize spiritual, ethical and social values. The opportunistic and conflict of interest assumptions in this theory are seen as incompatible with the principles of trust, tawhid, and maslahah that are at the core of Islamic economic ethics. This study aims to critically examine the epistemological structure of conventional agency theory and reformulate it into an Islamic value framework through a conceptual literature study approach and content analysis of Scopus, DOAJ, and SINTA indexed scientific literature in the period 1998-2025. The results of the study show that the Islamic Ethical Agency Framework (IEAF), which is built on four main pillars of tawhid, amanah, maslahah, and dual governance can be a more suitable theoretical alternative in bridging the principal-agent relationship ethically and transcendental. With IEAF, the Islamic financial system can be directed not only to achieve economic efficiency, but also encourage sustainable moral and social transformation. The findings provide an important conceptual contribution to the development of Islamic agency theory and the strengthening of Islamic value-based financial governance.